Abordaje de la sexualidad en las personas en tratamiento renal sustitutivo desde el punto de vista de pacientes y profesionales - Andrea Canillas-Sáez; Marta Natalia Gutiérrez-González; Maite González-Manjón; Virginia Fernández-Íñiguez de Heredia (Sociedad Española de Enfermería Nefrológica, 2023)
Introduction: Chronic kidney disease affects multiple areas of individuals' lives, with sexuality being one of them. Few studies analyze the approach taken by dialysis units on these aspects. Objetives: To analyze the perception of patients and professionals in dialysis units regarding the approach to sexuality in individuals undergoing dialysis. Material and Method: Cross-sectional descriptive observational study conducted between April and May 2022 in the Integrated Health Organization of Araba. Participants included patients undergoing dialysis (peritoneal dialysis and hemodialysis, both in-center and at home) and professionals (nurses, nursing care technicians, and physicians) from these units. They completed an ad-hoc questionnaire collecting sociodemographic data and aspects related to the approach to sexuality in individuals undergoing dialysis. Results: 20.2% of patients and 50.0% of the team participated. 67.7% of patients reported that the treatment had affected their sexual needs "much" or "to some extent." 66.7% of the team felt "not at all" or "not very" confident in addressing sexuality in this population. Conclusions: Sexuality is impacted in individuals undergoing renal replacement therapy with dialysis, and a significant portion of professionals do not feel confident in addressing this issue with them. Addressing this need remains an important area for improvement. It is necessary to provide professionals with the necessary tools to address this need.